A single dose multi-ingredient pre-workout supplement enhances upper body resistance exercise performance - Beyer, Kyle S.; Gadsden, Max; Patterson-Zuber, Patrick; Gonzalez, Adam M. (Frontiers in Nutrition, 2024)
Multi-ingredient pre-workout supplements (MIPS) are commonly used by individuals looking to enhance exercise performance and augment adaptations to training. However, the efficacy of commercially available MIPS is largely dependent on the ingredient profile, and new formulations should be investigated to determine their effectiveness. Therefore, the purpose of this study was to examine the effects of a commercially available MIPS product on performance during an upper body resistance exercise protocol. Twenty resistance-trained participants (10 men, 10 women) volunteered to complete this double-blind, placebo-controlled, crossover study consisting of 3 visits. Visit 1 consisted of body composition, 1-repetition maximum (1RM) testing, and familiarization. Visits 2 and 3 consisted of supplementation with either MIPS or placebo (PLA) 1-hour prior to completion of an upper body resistance exercise workout during which power output, repetitions completed, rating of perceived exertion (RPE), and perceived recovery were recorded. Assessments of reaction time, isometric mid-thigh pull, and perceived levels of focus, energy, fatigue, and "muscle pump" were also completed before supplementation, 1-hour after supplementation, and immediately after exercise. Statistical analysis revealed significant main effects of trial for reaction time (p<0.001) and bench press peak power (p=0.026) indicating better performance during the MIPS trial. Furthermore, total number of repetitions completed significantly increased (p=0.003) during the MIPS (96.90±21.31 repetitions) trial compared to PLA (89.50±18.37 repetitions). Additionally, overall session RPE was significantly lower (p=0.002) during the MIPS (7.6±1.2) trial compared to PLA (8.3±0.9). These findings suggest that acute supplementation with this MIPS improved upper body resistance exercise performance while reducing participant RPE. Further research should investigate the efficacy of chronic supplementation with this MIPS as the acute response provided an ergogenic benefit.